INDIVIDUAL VIEWS ON AGING IN THE CONTEXT OF SOCIAL CHANGE AND CULTURAL DIFFERENCES - Wurm, S. (Innov Aging, 2017)
Findings on the impressive impact of individual views of aging and old age (VoA) on health and longevity call for a better understanding of these views. Previous studies have examined VoA as well as preparation for age-related changes mainly on the individual level without broadening the perspective to contextual influences. In contrast and based on large-scale survey data, this symposium will look at how and why VoA are subject to social change, how they differ between different networks, countries and continents, and how this is able to affect preparation for age-related changes. Wurm and colleagues will go into the social change of different VoA across 18 years based on four waves of representative, cross-sectional data from the German Ageing Survey (1996 to 2014). Using longitudinal data from the same survey in combination with district-level information, Wolff et al. will examine whether changes in VoA depend on the pace of population aging on district level. Notthoff will look at the impact of the age structure of people’s social network on VoA and will examine cultural differences in this impact, based on data of the European Social Survey. Kornadt and colleagues will address cultural differences in preparation for age-related changes based on survey data from the U.S., Hong Kong and Germany. Finally, the discussion of Prof. Staudinger (Columbia University, New York) will focus on the significance of survey data for research on VoA and its potential implications for policy and practice.